Analisis Efektivitas Jaringan Bisnis pada Produk Salaut - Marselina, Resya Dwi; Maesyaroh, Siti; Nurbaeti, Azra Lutfiah; Febiansyah, Ilza Tio (Melati Institute, 2024)
This study examines the effectiveness of business networks in the food production of Salaut, a culinary business located in Pangandaran, Indonesia. Salaut specializes in seafood dishes and snacks, holding Intellectual Property Rights (IPR) and a Food Industry Household (PIRT) certification. Their organizational structure involves various departments, actively participating in both offline and online marketing. A SWOT analysis identifies the strengths, weaknesses, opportunities, and threats for Salaut. Solid partnerships with raw material suppliers have strengthened their foundation, while opportunities to enhance collaborations with suppliers and explore online distribution remain open. The article covers production, marketing, value addition, and financial reporting as key elements in the development of this culinary business.